Studying the Effects of Wave Dissipation Structure and Multiple Size Diffusion Chambers on Explosion Shock Wave Propagation - Wei Liu; Xiangyun Xu; Huahui Yi; Lifan Zhu (Fire, 2023)
Explosion chambers are crucial to the technology used to prevent coal mine gas explosions. Investigating the shock wave propagation law at various coal mine tunnel cross-sections helps ensure mine safety. A self-built, highly explosive experimental setup was used to conduct empirical research on straight tubes, eight sizes of single-stage explosion chambers, and multi-stage tandem explosion chambers. Ansys Fluent numerical simulation software constructed five different tandem explosion chamber models. The wave dissipation efficiency of various types of explosion chambers was calculated, the propagation law and process of shock waves across multiple explosion chambers were examined, and the best size and type of explosion chambers were summarized to increase the wave dissipation efficiency of single-stage explosion chambers. Gun silencers inspired these models. The findings indicate that the three-stage tandem explosion chamber is the best diffusion tandem combination form, the 60° silencer-type explosion chamber is the best single-stage explosion chamber modification program, and the 500 mm × 500 mm × 200 mm explosion chamber is the best single-stage explosion chamber.